Economic Sector Study and Development Strategy for the Rebana Metropolitan Area - Meliana, Chicha; Indriani, Fera; Firdaus, Qonita Afnani (Gorontalo Development Review, 2024)
This research analyzed potential sectors and development strategies in each city/regency in the Rebana Metropolitan Area, from 2018 to 2022. The research method used was quantitative descriptive using several analytical methods, namely Location Quotient, Shift Share, Labor Productivity Levels per Sector, and Klassen Typology. The research results show that each district/city in the Rebana Metropolitan Area has different economic characteristics, apart from that priority infrastructure projects and industrialization which are the direction of development of the Rebana Metropolitan Area have not had a significant impact on the progress of cities/regencies in the Rebana Metropolitan Area.